(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Interlocking Stabilized Soil Block (ISSB) technology is gaining ground in Nigeria as a sustainable, cost-effective alternative to conventional masonry, yet its aesthetic dimension has received little empirical scrutiny. This study assesses occupant satisfaction with the aesthetic qualities of selected ISSB residential buildings in Southwestern Nigeria, drawing on structured questionnaire data from 110 respondents across three estates in Ekiti, Ogun, and Lagos states. Descriptive statistics, Pearson correlation, and multiple regression analyses were applied using SPSS. Occupants expressed strong satisfaction with the environmental harmony, natural colour, and visual distinctiveness of ISSB buildings (mean scores of 4.05, 4.00, and 3.98 respectively), while surface finishing quality (2.87) and public perception (2.95) fell within the neutral range. The grand mean of 3.65 confirms general aesthetic satisfaction. Regression analysis identified environmental harmony as the strongest predictor of overall satisfaction (β = 0.298, p < 0.001), and surface finishing quality as a disproportionately influential weakness (β = 0.143, p < 0.05). Targeted improvements in finishing technique, architectural detailing, and public awareness are recommended to consolidate and extend ISSB's aesthetic appeal in the Nigerian housing market.